The development and analysis of the strained Si on relaxed Si₀.₇Ge₀.₃/Si N-MOS - Abbas, Mohd Hussaini (2007)
The electrical characteristics of the Si₀.₇Ge₀.₃ on relaxed Si N-MOS are compared with the conventional Si N-MOS developed by the simulation of basic fabrication processes. From the result, it will show that the Si₀.₇Ge₀.₃/Si N-MOS gives better performance than the Si N-MOS. Based on the simulated electrical characteristics, the strained SiGe/Si heterostructure influences the threshold voltage, Vt. From Id-Vg curve, the Si₀.₇Ge₀.₃/Si N-MOS has a 0.3V lower threshold voltage compare to conventional Si N-MOS means that reduction until 46.15% of Vt occur. The faster turn on of transistor is important to achieve a high speed in complementary MOS technology. The Si₀.₇Ge₀.₃/Si N-MOS are also developed in three n-channel lengths that are 1.2 urn, 1.0 um and 0.8 urn. The decreased of n-channel length will increase the saturated current. The term of low Vt and higher Id saturation as shown in Id-Vd curves means less power supply and faster to turn on. The threshold voltage of Si₀.₇Ge₀.₃/Si N-MOS can be reduced until 55.96% from conventional Si N-MOS and the figure keep regress when decreases the channel length.